Narcissism and Selfitis Disorder Features among Young Adults: Body Dysmorphic Disorder as Mediator: Narcissism and Selfitis Disorder Features among Young Adults - Aroosa, .; Bibi, Humaira; Naz, Summaira; Afsar, Faria Khan (Pakistan Journal of Health Sciences, 2023)
Nowadays young generations are involved in such activities which abolish their life seriously. In today’s world everyone wants to look flawless and wants to be praised. Objective: To investigate the mediating effect of body dysmorphic disorder on narcissism and selfitis disorder among young adults. Methods: The sample size for the present study was 400 young adults. Convenient sampling technique was used for screening of young adults on Body Image Concern Inventory and further data were collected on Selfitis Behavior Scale and Narcissistic Personality Inventory from screened sample. Inclusion criteria included all the young adults aged between 20 to 35 and have body dysmorphic disorder. Results: Narcissism had significant positive correlation with features of both selfitis disorder and body dysmorphic disorder. Age of persons had significant negative correlation with narcissism, selfitis disorder and features of body dysmorphic disorder. Outcomes revealed that both selfitis disorder and narcissism are greater in males, while features of body dysmorphic disorder are greater in females as compared to males. Conclusions: This study will be beneficial for professionals (sociologists and social workers) for creating awareness in young generation about flaws or defects in the physical appearance should not be considered as life frightening conditions and they should appreciate themselves as they are.